ANALISIS DIGITAL LEADERSHIP, KOMPETENSI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN JNE SUKABUMI - Halimah Nursiva; Ade Sudarma; Leonita Siwiyanti (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
If the goal is achieved well, the performance is declared a success. Overall, effective digital leadership, strong competencies, and a good work environment interact and influence each other to improve employee performance. However, many businesses, especially those related to freight forwarding services, face performance problems such as lack of knowledge about digital information technology, poor work environment, high turnover, and low discipline. All these problems disrupt company operations and performance. Therefore, this research aims to see how the performance of JNE Sukabumi branch employees is influenced by digital leadership, employee abilities and the work environment. It is hoped that this research will offer a new perspective on how to improve company performance and competitiveness in the technological era. This study utilizes a quantitative research model. In this research, probability sampling is used to collect data by distributing questionnaires and company data. The study's findings indicate that work environment, competency, and digital leadership all positively and significantly impact employee performance. Additionally, competency, work environment, and digital leadership all positively and significantly impact employee performance when taken together.